Outcomes with venoarterial vs venovenous extracorporeal membrane oxygenation as a bridge to lung transplantation in interstitial lung disease - Prasanth Balasubramanian, MD; Pablo Moreno Franco, MD; Sanjay Chaudhary, MBBS; Francisco G. Alvarez, MD; Maher Baz, MD; Tathagat Narula, MBBS; Sadia Z. Shah, MD, MBA; Mohammad Alomari, MD; Rohan Bongu, BS; Anirban Bhattacharrya, MD; Devang Sanghavi, MD; Sean Kiley, MD; et al. (JHLT Open)
Background: Evidence on outcomes associated with venoarterial (VA) versus venovenous (VV) of extracorporeal membrane oxygenation (ECMO) as a bridge to lung transplantation (LTx) in interstitial lung disease (ILD) is limited. Methods: Using the United Network for Organ Sharing (UNOS) Standard Transplant Analysis and Research (STAR) registry, we conducted a retrospective cohort study on ILD patients bridged with ECMO for LTx. Outcomes by cannulation type (VV vs VA) were analyzed, with 1:1 propensity matching to reduce selection bias. Results: Among 1,551 patients, 1,236 (79.7%) were on VV ECMO and 315 (20.3%) on VA ECMO. Delisting due to death or deterioration was higher with VA ECMO in both the overall (41% vs 27%, p < 0.001) and matched (41% vs 30%, p = 0.003) cohorts. VA ECMO was associated with higher 1-year post-transplant mortality in the overall cohort (33% vs 24%, p < 0.001), though not statistically significant in the matched cohort (33% vs 24%, p = 0.059). Multivariate Cox-proportional hazard regression analysis showed no significant difference in 1-year post-transplant mortality with VA ECMO in the overall (adjusted Hazard Ratio (aHR) 1.01 (95% confidence interval, CI 0.65-1.60, p > 0.9)) and matched (aHR 1.24, 95% CI 0.78-1.97, p = 0.4) cohorts, compared to VV ECMO. However, the VA ECMO had higher 1-year post-transplant mortality in the setting of COVID-19 associated pulmonary fibrosis (aHR 7.12, 95% CI 1.9-26.6, p = 0.003). Conclusions: VV ECMO was associated with a more successful bridge to LTx than VA ECMO. Adjusted post-transplant outcomes were comparable. Prospective studies are warranted to explore outcome differences by cannulation strategy in ILD.